Penggunaan Media Google Form Untuk Pemberian Tugas Matematika di SDS Az-Zahrah Pada Masa Pandemi - Handy Sugiarto; Siti Fauziyah; Agis Dwi Putri (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2021)
The purpose of this study is the use of the google form application as a fourth grade math assignment at sds az zahrah. This research uses qualitative research with a descriptive analysis method. The subjects of this study were 4th grade students at sds az zahrah, north jakarta. The data collection technique is in-depth interviews. Researchers collected various data by conducting an interview with research subjects related to learning mathematics using the google form and its constraints. The research instrument is an interview guide. The results in this study are that online learning using google forms, especially in giving math assignments, is considered to make it easier for students to work on and collect their math assignments. In addition, students become more enthusiastic in online learning. It was also found that there were students who had problems doing their assignments because they did not have a device.